The inflammatory injury in the striatal microglia-dopaminergic-neuron crosstalk involved in Tourette syndrome development - Wang, Xueming; Liu, Xiumei; Chen, Liangliang; Zhang, Xiaoling (Frontiers in Immunology, 2023)
Background: Tourette syndrome (TS) is associated with immunological dysfunction. DA system is closely related to TS development or behavioral stereotypies. Previous evidence has suggested that hyper-M1-polarized microglia may exist in the brains of TS individuals. However, the role of microglia in TS and their interaction with dopaminergic neurons is not clear. In this study, we applied iminodipropionitrile (IDPN) to establish a TS model and focused on the inflammatory injury in the striatal microglia-dopaminergic-neuron crosstalk. Methods: Male Sprague-Dawley rats were intraperitoneally injected with IDPN for 7 consecutive days. Stereotypic behavior was observed to verify the TS model. Striatal microglia activation was evaluated based on different markers and expression of inflammatory factors. The striatal dopaminergic neurons were purified and co-cultured with different groups of microglia, and the dopamine associated markers were assessed. Results: First, pathological damage to striatal dopaminergic neurons in TS rats, as indicated by decreased expression of TH, DAT and PITX3. Next, the TS group showed a trend of increased Iba-1 positive cells and elevated levels of inflammatory factors TNF-α and IL-6, as well as an enhanced M1-polarization marker (iNOS) and attenuated M2-polarization marker (Arg-1). Finally, in the co-culture experiment, the IL-4 treated microglia can up-regulate the expression of TH, DAT and PITX3 in the striatal dopaminergic neurons vs LPS treated microglia. Similarly, the TS group (microglia from TS rats) caused a decreased expression of TH, DAT and PITX3 in comparison with Sham (microglia from the control rats) in the dopaminergic neurons. Conclusion: In the striatum of TS rats, microglia activation is M1 hyperpolarized, which transmits inflammatory injury to striatal dopaminergic neurons and disrupts the normal dopamine signaling.